TANAMAN DALAM PENGATURAN RUANG KELAS UNTUK MENCIPTAKAN MEDIA DAN LINGKUNGAN PEMBELAJARAN YANG KONDUSIF - Novianti Muspiroh; Asep Kurniawan (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2014)
The learning process in schools mostly occurs in the classroom where students learn to interact for many hours. Meanwhile the condition of the class frequently does not support, classes are too crowded, hot, stuffy, and others. So complete sufferings of those who learn in them. In fact comfortable classrooms can ensure the achievement of effective learning. In this case, how can it be achieved? One of the frequently overlooked in classroom management, to create a learning conducive atmosphere, is the placement of plants. In addition to the aesthetic of class decoration, plants are useful to create the ideal temperature, produce oxygen for the needs of the students in class that are generally crowded, and clean up pollutants. Thereby, the class will be lovely and comfortable which ultimately will lead to a positive attitude and mind in learning. Kata Kunci: Tanaman, Kelas, Pembelajaran, Kondusif